# For f(x)=4x+1 and g(x)=x^2-5, find (f/g)(x)

For f(x)=4x+1 and g(x)=x^2-5, find (f/g)(x)

## This Post Has 10 Comments

1. rileysndr1782 says:

x^2 + 4x - 4.

Step-by-step explanation:

(f + g)(x) is the same thing f(x) + g(x), which is the same thing as (4x + 1) + (x^2 - 5).

(4x + 1) + (x^2 - 5)

= x^2 + 4x + 1 - 5

= x^2 + 4x - 4

Hope this helps!

2. csuggs8 says:

i hope this helps !

$For f(x)=4x+1 and g(x)=x^2-5, find (f•g)(x) Im stuck please help$

3. 10040813 says:

4X³+x²-20x-5

Step-by-step explanation:

(f•g)(x)=(4x+1)•(x²-5)=4x³-20x+x²-5

4. Carrchris021 says:

00

step-by-step explanation:

5. kyraj21 says:

Step-by-step explanation:

(f+g)(x) = f(x) + g(x)

= 4x + 1 + x² - 5

= x² + 4x  - 4

6. hellicuh says:

x^2 +4x -4

Step-by-step explanation:

f(x) = 4x+1

g(x) = x^2-5

(f+g)(x) =  4x+1 + x^2 -5

Combine like terms

= x^2 +4x +1-5

=x^2 +4x -4

7. hhomeschool24 says:

(f + g)(x) is x² + 4x - 4

Step-by-step explanation:

Step 1:

Given f(x) = 4x + 1, g(x) = x² - 5. Find (f+g)(x)

(f + g)(x) = f(x) + g(x) = 4x + 1 + x² - 5 = x² + 4x - 4

8. ragegamer334p3xlso says:

The answer is A, x^2 + 4x - 4

Just did this in calculus last year. It's really simple, you just add them together.

(f+g)(x)

x^2 - 5 + 4x + 1

x^2 + 4x - 4

Good luck!

9. ijustneedhelp29 says:

4(x^2-5)+1 --> the answer is 4x^2 - 19

10. lordcaos066 says: